Environmental Impacts of Tartaric Stabilisation Processes for Wines using Electrodialysis and Cold Treatment - Bories, A.; Sire, Y.; Bouissou, D.; Goulesque, S.; Moutounet, M.; Bonneaud, D.; Lutin, F. (South African Journal of Enology and Viticulture, 2016)
The environmental impacts of the two tartaric stabilisation methods used for wines, electrodialysis and cold treatment, were studied by determining water consumption (for the process and cleaning), waste produced (organic load and the composition of wastewater and residues) and energy consumption, at the pilot stage and in wineries. Thanks to an online treatment of electrodialysis brines by reverse osmosis (industrial facility that treats 30 hL wine/h), the recycling of permeates led to a 65% reduction in water consumption, the volume of which represented only 3.9% of the wine treated. When washing and cleaning water from the ED-RO system was taken into account, overall water consumption was 5.5 L/hL wine. The presence of ethanol, due to an osmotic phenomenon with no loss of wine volume, and tartaric acid in the brines contributes to the organic load of the brine, with a COD of close to 8.4 g O2/L. Overall electrical energy consumption for stabilisation by electrodialysis (0.21 kWh/hL) turned out to be eight times lower than that of cold stabilisation. An evaluation of cold stabilisation effluents revealed that 66.6% of the COD discharged came from the diatomaceous earth (DE), 21.8% from the washing of the filter and 11.4% from the washing of the cold treatment tank. The production of used DE was 2.64 g (wet weight)/L of wine, and the ethanol present in the DE waste represented a loss in wine volume of 0.14 L/hL.